PTU-143 Comparison of clinical effectiveness and compliance with transanal irrigation treatment: neurogenic v.s. functional bowel disorders. (8th June 2018) - Yiu, J; Pesce, M; Storrie, J; Emmanuel, A; Zarate, N
Abstract : Introduction: Transanal irrigation (TAI) has emerged as one of the therapeutic strategies in managing constipation and faecal incontinence in neurogenic bowel disorders (NBD). It is unclear whether patients with functional bowel disorders (FBD), particularly irritable bowel syndrome with constipation (IBS-C), refractory to standard therapies might benefit from TAI. We aimed at retrospectively assessing and comparing the effectiveness and compliance with TAI in patients with NBD and FBD. Methods: A retrospective review of selected NBD and FBD patients referred for TAI treatment at University College Hospital between 2013–2017 was carried out. Co-morbidities, medications and patients experience with TAI were evaluated. Clinical impact was assessed using the neurogenic bowel dysfunction score (NBDS). Intra-group comparison pre-TAI and post-TAI were performed. Results: 63 patients (mean age 50 years, 45 females) were reviewed. 39 patients had neurogenic bowel dysfunction, mostly multiple sclerosis and spinal cord injury, whereas 24 patients had IBS-C based on Rome III criteria. Depression was the most frequently reported comorbidity (8% and 29% of NBD and IBS-C, respectively). At baseline 82.5% of patients were taking conventional laxatives and chronic use of opioids was comparable between the groups (26% and 21% for NBD and IBS-C, respectively). Overall 37 patients (14 IBS-C and 23 NBD) were compliant to TAI at follow up. The mean NBD scores significantly improved in the whole cohort (10.8 v s 8.3 post-treatment; p=0.01). NBD scores significantly improved for IBS-C patients (12.9 vs 8.9; p=0.02) but not for the neurogenic ones (9.5 vs 8; p=0.09). Patients with IBS-C reported more infrequent bowel movements/week compared to NBD patients (2±1 vs 4±2, respectively). Post-TAI treatment, the average number of bowel movements/week increased in both groups (3 vs 2 and 5 vs 4 for IBS-C and NBD, respectively). Of the initial cohort, 17 patients (7 IBS-C and 10 NBD) were lost at follow up; whilst 9 patients (3 IBS-C and 6 NBD) abandoned the treatment. The main reasons for withdrawal were inefficacy of the treatment (66.7%) followed by TAI-related side effects in a third of patients. NBD patients reported a greater improvement in QoL whilst better bowel function control and more frequent bowel movements were the main reasons for continuing TAI therapy in IBS-C patients. Conclusions: TAI is an effective treatment for bowel dysfunction in patients with FBD showing a similar efficacy to that of the NBD group. Although larger prospective data are needed to validate these results, TAI should be considered as an effective strategy in managing patients with FBD, for whom traditional treatments have failed.